Approximation Of Improper Integral Based On Haar Wavelets - Mohammad Hasan Abdul Sathar; Anvarjon A. Ahmedov; Nor Fadzillah Mokhtar; Ahmad Fadly Nurullah Rasedee (Journal of Multidisciplinary Engineering Science and Technology, 2024)
Previous numerical methods for solving definite integrals based on Haar wavelets was introduced. In this research we extend the previous works by approximate the solution of improper integral based on Haar wavelets functions. Error analysis of the approximation by Haar wavelets are given. Numerical examples are conducted to show the accuracy of the method.